Discursive constructions of professional identity in policy and regulatory discourse. (23rd July 2018) - Fealy, Gerard; Hegarty, Josephine‐Mary; McNamara, Martin; Casey, Mary; O'Leary, Denise; Kennedy, Catriona; O'Reilly, Pauline; O'Connell, Rhona; Brady, Anne‐Marie; Nicholson, Emma
Abstract: Aim: To examine and describe disciplinary discourses conducted through professional policy and regulatory documents in nursing and midwifery in Ireland. Background: A key tenet of discourse theory is that group identities are constructed in public discourses and these discursively constructed identities become social realities. Professional identities can be extracted from both the explicit and latent content of discourse. Studies of nursing's disciplinary discourse have drawn attention to a dominant discourse that confers nursing with particular identities, which privilege the relational and affective aspects of nursing and, in the process, marginalize scientific knowledge and the technical and body work of nursing. Design: We used critical discourse analysis to analyse a purposive sample of nursing and midwifery regulatory and policy documents. Method: We applied a four‐part, sequential approach to analyse the selected texts. This involved identifying key words, phrases and statements that indicated dominant discourses that, in turn, revealed latent beliefs and assumptions. The focus of our analysis was on how the discourses construct professional identities. Findings: Our analysis indicated recurring narratives that appeared to confer nurses and midwives with three dominant identities: "the knowledgeable practitioner, " the "interpersonal practitioner" and the "accountable practitioner." The discourse also carried assumptions about the form and content of disciplinary knowledge. Conclusions: Academic study of identity construction in discourse is important to disciplinary development by raising nurses' and midwives' consciousness, alerting them to the ways that their own discourse can shape their identities, influence public and political opinion and, in the process, shape public policy on their professions.